Analisis modal kerja untuk meningkatkan profitabilitas - Yuniar Ambarwati; Hermi Sularsih; Datuk Maralelo Siregar (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The research objective was to determine the working capital management of UD. Nila Kencana and to see the management of working capital in increasing the profitability of UD. Nila Kencana. In this study, the type of research chosen is descriptive research with a quantitative approach or field research, which is a research method that is inductive, objective, and scientific in which the data obtained is in the form of numbers or statements that are scored, and analyzed by analysis. statistics. The results showed that the level of networking capital increased in 2017-2018. Management of current and current assets in an effective way using the right policies will provide results in the form of profits that are planned for working capital management in 2016-2017 which is effective with working capital management balanced with an increase in company profits. Meanwhile, in 2017-2018 the effectiveness of increasing working capital was not matched by an increase in company profits. Meanwhile, in 2017-2018 the effectiveness of increasing working capital was not matched by an increase in company profits. This is due to an increase in the cost of goods manufactured which indicates an increase in the level of purchases in 2018 and has an impact on the cost of goods sold. Keywords: Working capital, Profitability, Financial ratio